Evaluation of the Pozzolanic Activity of Uncontrolled-Combusted Sewage Sludge Ash - Istuque, Danilo Bordan [UNESP]; Reig, Lucia; Soriano, Lourdes; Borrachero, Maria Victoria; Pinheiro Melges, José Luiz [UNESP]; Akasaki, Jorge Luis [UNESP]; Bernabeu, Jorge Juan Payá; Tashima, Mauro Mitsuuchi [UNESP] (American Society of Civil Engineers (ASCE), 2021)
Waste management is a crucial issue facing modern society. The generation of sewage sludge is increasing annually due to the urbanization and improvement of sanitation systems of cities. The construction sector has emerged as a solution for the elimination of waste due to the enormous volume of materials that this sector can absorb. This paper evaluates the pozzolanic activity of sewage sludge ash (USSA) obtained following an uncontrolled-combustion process, a simple and economic procedure. Compressive strength of Portland cement/USSA mortars with 5%-25% by weight USSA were evaluated. Calcium hydroxide/USSA and Portland cement/USSA pastes were chemically and physically characterized through thermogravimetric/differential-thermogravimetric (TG/DTG), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses. The increase in the replacement of Portland cement by USSA is associated with an increase in the compressive strength of mortars. These values for USSA containing mortars cured for 90 days were in the range of 49.6-55.4 MPa, higher than the one reached by the reference mortar. According to the microstructural analysis, the increment on the compressive strength can be attributed to the formation of hydrated products (C-S-H, C-A-S-H, and C-A-H) by the pozzolanic reaction of USSA.
Keywords: Fixed portlandite; Pozzolan; Sewage sludge ash (USSA); Uncontrolled combustion; Waste valorization